The Influence of Various Types of Physical Activity on Blood Pressure. A Literature Review - Wojciech Kołodziej; Dominika Mańdziuk; Michał Żuchowski; Patrycja Niewinna; Przemysław Zaroda; Paweł Dąda; Klaudia Kołodziej; Monika Korga; Jakub Wawrzkowicz; Paweł Pawlik (Nicolaus Copernicus University in Toruń, 2024)
Blood pressure is a key indicator of cardiovascular health, playing a significant role in the diagnosis, prevention, and treatment of heart and vascular diseases. In recent years, interest in the influence of physical activity on blood pressure has increased among researchers and health-conscious individuals. Among the studies presented, researchers examined the effects of various types of physical activity on blood pressure in individuals with hypertension and the level of hypertension control, as well as other components affecting the overall health of patients, such as blood lipid levels, arterial pressure variability over 24 hours, and BMI. The conclusions of the presented studies seemed to be consistent regarding the positive impact of engaging in physical activity on blood pressure and thus the better well-being of patients.